ENGLISH TEACHING - LEARNING PROCESS REALIZATION AND QUESTION BASED AS AN ALTERNATIVE ENGLISH TEACHING MODEL TO BUILD STUDENTS’ CHARACTER AT SMPN PADANG - Ernati Ernati (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Nobody denies that the main purpose of teaching English, as a foreign language, in Indonesia especially, is the learners are able to use English to communicate. In fact, it is found that most of students know much about English but when they are asked to use it in communication, they cannot, even their pronunciation in reading is still poor. They aren’t also be able to ask question to the interlocutor. These can be caused by many factors; one of them is the teachers do not make students accustomed to use English in the classroom. It also happens at SMPN Padang, The English teacher and students often do code switching to Indonesia, so the students are not accustomed to use English. Based on that finding, it is wise to implement “question based” model in teaching English as an alternative teaching model to improve the students’ capability to use English as communication and to build the students’ character of self confidence and critical thinking. Keywords: Character, question-based model, ELT